Narrativas de violência de gênero em acórdãos do STJ sobre Lei Maria da Penha - Freitas, Lúcia; Pinheiro, Veralúcia (Language and Law / Linguagem e Direito, 2017)
In this article, we discuss the problem of gender violence, as it is narrated and administered by the second highest Court of Justice in Brazil, the Superior Court of Justice (STJ). Based on a corpus of judgments covering nearly a decade that fall under the legislation of the Maria da Penha Law, we analyse narratives in two specific dimensions: 1) the narrative of the procedural trajectory of a particular case of violence, which can only be inferred from the complete reading of the judgment; 2) the mini narratives of the case that generated the processes and which are embedded within this broader narrative. From a discursive analysis that combines narrative, gender studies and feminist theories of law, we discuss the problematic relationship that exists between the premises based on the category “gender” that is that foundation of the law, and the norms of “gender” that guide the practices of the Brazilian judiciary.